Data warehousing and business intelligence for e-Commerce - Simon, Alan 1958- (2001)
You go online to buy a digital camera. Soon, you realize you've bought a more expensive camera than intended, along with extra batteries, charger, and graphics software-all at the prompting of the retailer. Happy with your purchases? The retailer certainly is, and if you are too, you both can be said to be the beneficiaries of "customer intimacy" achieved through the transformation of data collected during this visit or stored from previous visits into real business intelligence that can be exercised in real time. Data Warehousing and Business Intelligence for e-Commerce is a practical explorati
Includes index. - Includes bibliographical references and index. - Print version record
Keywords: Electronic commerce; Business intelligence; Data warehousing; Industrial marketing; Commerce électronique; Entrepôts de données (Informatique); Marketing industriel; BUSINESS & ECONOMICS; International; Marketing; BUSINESS & ECONOMICS; Marketing; Multilevel; BUSINESS & ECONOMICS; Exports & Imports